INFORMAL SHAPES OF SOCIAL ANOMIE - Stanković, Vladan; Perić-Dilegenski, Tijana (Serbian political thought, 2023)
The topic of this scientific work is placed in the domain of social anomie. The effects of the action of informal forms of social anomie cause social entropy and indicate the permanent topicality of the topic. Social anomie destroys social processes, devalues institutions and devastates the fundamental values on which the community rests, so the social significance of research is unquestionable. Scientific justification is contained in the need to shed light on phenomena and processes from the domain of social pathology. The aim of the research is to define, classify, sistematize the observed phenomena and to offer optimal solutions to overcome them. The work for the Subject of reserch has: discovering the forms of social anomie, pointing out the harmful effects of these informal forms of social behavior, as well as proposing solutions to overcome the resulting situation in order to remove the harmful effects. In their work, the authors start from: the observation method, the development method, the comparative approach, the cross-cultural method, and the numerous methods of legal sciences. The subject framework of the research moves in the area of: sociology, social pathology, political and legal sciences. We have explained the logic of various forms of institutional action that cause social anomie and violate the basic rules of behavior on which a community rests. Anomic conditions point to illegal activity and violation of basic legal acts. And yet, social anomie goes beyond legal frameworks, pointing to the lack of social rules in regulating social relations that escape legal sanctions. Therefore, it is important to have a collective consciousness, which, among other things, distinguishes the value and moral elements of a community. Public opinion, public pressure, sense of responsibility, institutional procedures, as well as the rule of law, direct actors-in-situation towards those behaviors that significantly reduce anomic conditions.